Perfil de sensibilidade e multirresistência em linhagens de Escherichia coli isoladas de infecção do trato urinário, de piometra e de fezes de cães - Siqueira, A.K. [UNESP]; Ribeiro, M.G. [UNESP]; Salerno, T. [UNESP]; Takahira, Regina Kiomi [UNESP]; Lopes, Maria Denise [UNESP]; Prestes, N.C. [UNESP]; Silva, A.V. (Universidade Federal de Minas Gerais (UFMG), Escola de Veterinária, 2008)
Susceptibility profile and multiple drug resistance in 158 E. coli strains isolated from urinary tract infection (UTI), pyometra, and feces of dogs were studied. Norfloxacin, ciprofloxacin, and enrofloxacin were the most-effective drugs (>60%) for E. coli strains. High rates of resistance to antimicrobials were observed in 60% or more of the isolated strains using sulfametoxazole/trimetoprim. Multiple drug resistance for three or more antimicrobials was observed in two (47.1%) strains isolated from UTI, seven (13.5%) from pyometra, and four (7.3%) from feces. From these, 17 (33.3%), one (1.9%), and three (5.5%), respectively, showed multiple resistance to five or more drugs.
Sensitivity profile and multiresistance in Escherichia coli strains isolated from urinary tract infection, pyometra and feces of dogs
Keywords: cão; E. coli; sensibilidade antimicrobiana; infecção do trato urinário; piometra; dog; E. coli; antimicrobial susceptibility; urinary tract infection; pyometra